Free food - some possibility : service recovery strategies in western based fast food restaurant / Ernest Cyril de Run and Liew Li Tyng - Cyril de Run, Ernest; Liew, Li Tyng (University Publication Centre (UPENA), 2007)
This paper sets out to determine customers belief of what service recovery activities will most probably be done by front liners in Western based fast food restaurants. The study used a Juster scale based questionnaire survey format the restaurants customers. Data was then analyzed using means and factor analysis. Factor analysis indicated three views of customers termed as Spoken, Minor Action, and Major Action service recovery strategies. Means indicate that customers believe that there is a good possibility for Spoken service recovery activity, fair possibility of Minor Action service recovery and some possibility of Major Action service recovery activity. Customers indicated that they did not expect front liners to offer free food and refunds but it was very probable that they would receive an apology. The study was limited to respondents in Kuching. Nevertheless the finding has important implications to management and academia. A practical application from this study would be the use of Minor or Major Action service recovery strategies to improve customer's perception of a company after service failure.